The effectiveness of a dual-component regimen of induction chemotherapy in the treatment of HPV-positive oropharyngeal squamous cell carcinoma - P. V. Golubev; L. V. Bolotina; A. R. Gevorkov; T. I. Deshkina; A. V. Boyko; A. D. Kaprin (Сибирский онкологический журнал, 2023)
Given the favorable prognosis associated with HPV-positive oropharyngeal cancer, cancer care professionals are actively discussing the feasibility of de-escalating treatment strategy for this cohort of patients.The purpose of the study was to improve the treatment outcomes in patients with locally advanced HPV- positive oropharyngeal squamous cell carcinoma by identifying the optimal induction chemotherapy (ICH) regimen, in particular, by using a two-drug ICH.Material and Methods. The study included 27 patients with locally advanced (T3–4N0–1, or T1–4N2–3) P16-positive oropharyngeal squamous cell carcinoma. All patients received 3 cycles of ICT according to the TP (docetaxel + cisplatin) regimen. To assess the effect and toxicity of two-drug ICH, a control group of patients, who received ICH according to the standard three-drug TPF (docetaxel, cisplatin and 5FU) regimen, was formed.Results. In the TP group, complete response (CR) was achieved in 3 (11 %) patients, partial response (PR) in 17 (63 %), stable disease (SD) in 7 (26 %) patients. In the control group: CR 4 (20 %) patients, PR – 13 (60 %), SD – 4 (20 %) patients. The median follow-up time in the TP group was 9 months (range: 2 to 22 months). The 1-year progression-free (PFS) and overall survival (OS) rates were 88.2 % and 100 %, respectively. In the TPF group, the PFS and OS rates were 84.4 % and 100 %, respectively.Conclusion. The results revealed that TP ICH regimen was non-inferior to the standard TPF regimen in the rates of the objective response, 1-year OS and PFS.